Implementation of Employment Policy in Rokan Hilir Regency (Study on Local Labor Placement in Upstream Oil and Gas Businesses): Implementasi Kebijakan Penyelenggaraan Ketenagakerjaan di Kabupaten Rokan Hilir (Studi Penempatan Tenaga Kerja Lokal pada Usaha Hulu Migas) - Yusuf, Muhammad; As’ari , Hasim (Universitas Muhammadiyah Sidoarjo, 2025)
Regional Regulation No.8 of 2014 on the Implementation of Workers in Rokan Hilir Regency to apply the priority quota for 60 percent. This of course is not a good situation for workers in the upstream oil and gas sector, especially following the handover of operations of PT Pertamina Hulu Rokan (PHR). Applying the Van Meter and Van Horn framework with descriptive qualitative methods, this article aims to gain a textured understanding of the policy's implementation. These results further suggest that failure to reach the 60 percent objective is an institutional one, thus failing in several aspects of policy implementation. Among the various problems are: (1) low authority; (2) lack of oversight from Disnaker as executive, causing it to be regarded as a normative document only; (3) huge skill gapbut poor training and inadequate training given to workers, demonstrating the minimal coordination towards non-transparent recruitment passage through informal channels that encourages nepotism and not even public acknowledgment for local human resources. The permissive position of the local government and the low (disposition) of enterprise are also obstacles. In conclusion, the scheme itself signifies the pressing requirement of institutional strengthening, obligatory certification programs and prompt and rational benefits that are yet to be claimed in order to enhance local labor welfare by also keeping open the main employment gateway for compliance.